Are antidepressants effective? A debate on their efficacy for the treatment of major depression in adults. (2nd April 2016) - Bschor, Tom; Kilarski, Laura L.
ABSTRACT: Recently, the efficacy of antidepressants, a treatment used by 11% of US American adults, has been debated. Thousands of randomized controlled trials (RCTs) have been used to study antidepressants, with the majority demonstrating at least moderate superiority over placebo. In contrast, studies have found antidepressant effects to be unspecific and mainly resulting from placebo. The effects of antidepressants may also be overestimated due to selective publishing and selection of patients who have a high chance of response in RCTs. Studies have also shown the drugs do not reduce suicidal events when compared to placebo, and efficacy differences to placebo are often too small to prove clinical relevance. Here, we review the claims for and against antidepressant efficacy.